The induction of puberty in female Boer goat kids - Greyling, J.P.C. (International Livestock Research Institute, 1996)
The effects of season, nutrition and presence of a ram at the onset of puberty in female Boer goat kids were studied. Permanent presence of a vasectomised ram with the female goat kids induced puberty earlier (P<0.05) than when the teaser ram was introduced to the female goat kids twice daily. Exposure of female goat kids to a higher energy diet tended to also induce puberty earlier but this influence did not differ much (P>0.05) from female goat kids put on a low energy diet. Female Boer goat kids born in summer and weaned in autumn attained puberty earlier (P<0.05) than those born in spring and weaned in summer. The results of this study suggest that the reproductive functions, such as puberty, in female Boer goat kids can be manipulated through management techniques such as permanent exposure to the ram, good nutrition and strategic weaning and breeding.